2005
DOI: 10.1029/2004jc002602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ciliated protozoa and heterotrophic nanoflagellates on the fate of primary production in the northeast Atlantic Ocean

Abstract: [1] Heterotrophic nanoflagellates and ciliates and their herbivorous activity were studied within the framework of the Programme Océan Multidisciplinaire Méso Echelle (POMME) in the northeastern Atlantic between 16°-22°W and 38°-45°N during winter, spring, and late summer/autumn 2001. Ciliate ingestion rates of Synechococcus and eukaryotic algae were measured using fluorescently labeled prey. Heterotrophic nanoflagellate ingestion rates of Synechococcus and Prochlorococcus were also estimated. Heterotrophic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…Virtually all studies of microbial dynamics during the North Atlantic spring bloom have identified microzooplankton as active and important grazers (Burkill et al 1993, Verity et al 1993b, Gifford et al 1995, consuming much of the daily primary production (StelfoxWiddicombe et al 2000, Fileman & Leakey 2005, Karayanni et al 2005. The microzooplankton community is typically dominated by aloricate ciliates (Verity et al 1993b, Stoecker et al 1994, Fileman & Leakey 2005 and, less frequently, by heterotrophic dinoflagellates and tintinnids (Verity et al 1993a, Stelfox-Widdicombe et al 2000.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Virtually all studies of microbial dynamics during the North Atlantic spring bloom have identified microzooplankton as active and important grazers (Burkill et al 1993, Verity et al 1993b, Gifford et al 1995, consuming much of the daily primary production (StelfoxWiddicombe et al 2000, Fileman & Leakey 2005, Karayanni et al 2005. The microzooplankton community is typically dominated by aloricate ciliates (Verity et al 1993b, Stoecker et al 1994, Fileman & Leakey 2005 and, less frequently, by heterotrophic dinoflagellates and tintinnids (Verity et al 1993a, Stelfox-Widdicombe et al 2000.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The factors 49, 250, 671, 2100 and 3498 fg C cell −1 were used to convert Prochlorococcus, Synechococcus, picoeukaryotes, nanocyanobacteria and nanoeukaryotes, respectively (Cailliau et al, 1996;Kana and Glibert, 1987;Campbell and Yentsch, 1989;Karayanni et al, 2005).…”
Section: Flow Cytometry (Fcm) and Carbon Biomassmentioning
confidence: 99%
“…Tintinnid ciliates are characterized by the possession of a tube or vase-shaped shell or lorica into which the ciliate cell can contract. They are generally a minority component of the microzooplankton, representing 5-10% of ciliate numbers (e.g., Dolan and Marassé, 1995) but occasionally dominate the microzooplankton (Karayanni et al, 2005). Tintinnids, as loricate choreotrich ciliates, are considered a monophyletic group in traditional ciliate classification schemes (Lynn and Small, 2000) and based on results of molecular work (e.g., Agatha and Strüder-Kypke, 2007;Agatha et al, 2005;Snoeyenbos-West et al, 2002).…”
Section: Introductionmentioning
confidence: 99%